Utilizing the Hub-and-Spoke Model to Deliver Quality Breast Imaging in a Large Health System. Issue 1 (13th March 2019) - Pham, Ramya; Constantinou, Niki; Plecha, Donna
Abstract: Healthcare systems are constantly expanding and gaining new territories. This growth is met with challenges in the organization and delivery of quality health care services to a large geographical area. The need for provider and staff coverage at the new sites often outpaces the rate at which additional providers and staff are hired. The need for new technology, equipment, and administrative support to oversee the new sites may also lag. The overall result could compromise patient experience at these outlying locations. The breast imaging division at University Hospitals Cleveland Medical Center (UHCMC) instituted many changes to support UHCMC's continual growth while focusing on consistent quality of care and optimal patient experience. Changes included adoption of the hub-and-spoke organization-design model and incorporation of the integrated practice unit (IPU) concept. In the hub-and-spoke organization-design model, full services are offered at a central hub, with additional limited services provided at the peripheral spoke sites. The IPU is a dedicated team of clinical and nonclinical personnel providing the full care cycle centered on a specific medical condition such as breast health. The breast imaging hubs and spokes are incorporated into the breast health IPUs to provide uniform quality care across a large health system. The purpose of this article is to describe how the breast imaging division, functioning as members of the breast care IPU, utilized the hub-and-spoke concept to provide quality breast imaging services throughout the expanding health system.